2019
DOI: 10.1186/s13756-019-0525-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection after craniotomy: a prospective cohort study

Abstract: Background Although surgical site infection after craniotomy (SSI-CRAN) is a serious complication, risk factors for its development have not been well defined. We aim to identify the risk factors for developing SSI-CRAN in a large prospective cohort of adult patients undergoing craniotomy. Methods A series of consecutive patients who underwent craniotomy at a university hospital from January 2013 to December 2015 were prospectively assessed. Demographic, epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 36 publications
7
43
5
2
Order By: Relevance
“…Reponen et al reported that high ASA scores are associated with increased systemic and infectious complications [17]. A more recent study has confirmed that high ASA scores are one of the independent risk factors for surgical site infection after craniotomy [18]. In the present study, the rate of systemic infections was higher in the high ASA than in the low ASA group, but the difference was not significant.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Reponen et al reported that high ASA scores are associated with increased systemic and infectious complications [17]. A more recent study has confirmed that high ASA scores are one of the independent risk factors for surgical site infection after craniotomy [18]. In the present study, the rate of systemic infections was higher in the high ASA than in the low ASA group, but the difference was not significant.…”
Section: Discussioncontrasting
confidence: 41%
“…Increased postsurgical complications in patients with glioma with low KPS have been reported by several groups [4,[9][10][11]. In addition, the American Society of Anesthesiologists (ASA) score, which is a widely used clinical preoperative physical status classification, is a well-known risk factor for preoperative mortality and complications after craniotomy in patients with various brain tumors [12][13][14][15][16][17][18]. However, little is known about the impact of KPS and ASA scores in patients who undergo craniotomy for recurrent glioma.…”
Section: Introductionmentioning
confidence: 99%
“…The agent most commonly used for embolization has been 150-250 µm polyvinyl alcohol particles [14,19,36]. Some operators have also used 15-20% n-butyl-2-cyanoacrylate (NBCA) particles [8].…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Similarly, nosocomial infection rates (7.4%) and surgical site infection rates (1.8%) were lower when compared with other published results. 30,31 The occurrence of any adverse event (14.5%) appears to be low; however, it is challenging to appropriately compare, as it is highly dependent on which events are included in this cumulative variable.…”
Section: Discussionmentioning
confidence: 99%